Flight model performance test results of a helium dewar for the soft X-ray spectrometer onboard ASTRO-H. (March 2016) - Yoshida, Seiji; Miyaoka, Mikio; Kanao, Ken'ichi; Tsunematsu, Shoji; Otsuka, Kiyomi; Hoshika, Shunji; Mitsuda, Kazuhisa; Yamasaki, Noriko; Takei, Yoh; Fujimoto, Ryuichi; Sato, Yoichi; DiPirro, Mike; et al.
Highlights: We developed a hybrid cooling system by using liquid helium, mechanical coolers. We had improved the thermal performance from the engineering model. The lifetime of the helium is more than 3 years with 30 L of liquid helium. Abstract: ASTRO-H is a Japanese X-ray astronomy satellite, scheduled to be launched in fiscal year 2015. The mission includes a soft X-ray spectrometer instrument (SXS), which contains an X-ray micro calorimeter operating at 50 mK by using an adiabatic demagnetization refrigerator (ADR). The heat sink of the ADR is superfluid liquid helium below 1.3 K. The required lifetime of the superfluid helium is 3 years or more. In order to realize this lifetime, we have improved the thermal performance from the engineering model (EM) while maintaining the mechanical performance. Then, we have performed a thermal test of the flight model (FM). The results were that the heat load to the helium tank was reduced to below 0.8 mW in the FM from 1.2 mW in the EM. Therefore, the lifetime of the superfluid helium is more than 3 years with 30 L of liquid helium. In this paper, the thermal design and thermal test results are described.